2016
DOI: 10.1161/jaha.116.003769
|View full text |Cite
|
Sign up to set email alerts
|

Association of Age at Menopause With Incident Heart Failure: A Prospective Cohort Study and Meta‐Analysis

Abstract: Background Early age (<45 years) at menopause has been postulated to be associated with increased cardiovascular disease risk; however, evidence of its relation with heart failure ( HF ) incidence is limited. We examined whether age at menopause is associated inversely with HF incidence in the Atherosclerosis Risk In Communities ( ARIC ) study and summarized all existing data in a meta‐analysis. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 57 publications
3
64
0
2
Order By: Relevance
“…Even though this is the first study comparing the metabolic pathway for Ang II formation in freshly isolated CMs and NCMs in cardiac plasma membranes extracted from hearts of gonadal‐intact and ovariectomized hypertensive and normotensive rats, it remains to be determined whether the same differential results may be obtained in older animals. On the other hand, the clinical significance of the current findings is underscored by recent reports documenting that early onset menopause is, indeed, linked to incident HF later in life (Appiah et al, ; Ebong et al, ). In addition, there is a strong body of evidence implicating a significant contribution of local tissue‐derived cardiac and vascular RAS in age‐related remodeling (Strait & Lakatta, ).…”
Section: Limitationsmentioning
confidence: 58%
“…Even though this is the first study comparing the metabolic pathway for Ang II formation in freshly isolated CMs and NCMs in cardiac plasma membranes extracted from hearts of gonadal‐intact and ovariectomized hypertensive and normotensive rats, it remains to be determined whether the same differential results may be obtained in older animals. On the other hand, the clinical significance of the current findings is underscored by recent reports documenting that early onset menopause is, indeed, linked to incident HF later in life (Appiah et al, ; Ebong et al, ). In addition, there is a strong body of evidence implicating a significant contribution of local tissue‐derived cardiac and vascular RAS in age‐related remodeling (Strait & Lakatta, ).…”
Section: Limitationsmentioning
confidence: 58%
“…Prior data have suggested that women with early menopause, and consequently a shorter reproductive period with fewer reproductive cycles and lower cumulative exposure to endogenous sex hormones, have an increased risk of CHD, stroke, and possibly HF (47). An analysis of the Framingham Heart Study population suggested that the increased CHD risk with early menopause may be influenced by a loss of the protective effects of endogenous sex hormones and an increase in thrombotic risk (27).…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects of menstrual cycles are frequently hypothesized to explain why premenopausal women have a lower risk of cardiovascular disease (CVD) compared with postmenopausal women of similar age, although this is still a controversial hypothesis (2,3). Moreover, data suggest that women with early menopause have an elevated risk of coronary heart disease (CHD) and stroke, and there are conflicting data as to whether early menopause also predicts HF (47). …”
mentioning
confidence: 99%
“…Second, information on age at menopause and menarche, parity, and use of hormone replacement therapy, were not consistently available from charts. In developed countries, the average age of natural menopause of 51 years is used as a reference in cardiovascular studies, 39 and we interpreted our data with this knowledge. Third, while we were able to restrict our analysis to patients with less than 50% stenosis to exclude patients with higher plaque volumes given the correlation of stenosis with plaque volume, 24 our analyses were not adjusted for degree of stenosis.…”
Section: Discussionmentioning
confidence: 99%